Application of Ambr15 system for simulation of entire SARS‐CoV‐2 vaccine production process involving macrocarriers. (10th June 2022) - Jayson, Avital; Goldvaser, Michael; Dor, Eyal; Monash, Arik; Levin, Lilach; Cherry, Lilach; Lupu, Edith; Natan, Niva; Girshengorn, Meni; Epstein, Eyal; Rosen, Osnat
Abstract: The Ambr15 system is an automated, high‐throughput bioreactor platform which comprises 24 individually controlled, single‐use stirred‐tank reactors. This system plays a critical role in process development by reducing reagent requirements and facilitating high‐throughput screening of process parameters. However, until now, the system was used to simulate processes involving cells in suspension or growing on microcarriers and has never been tested for simulating cells growing on macrocarriers. Moreover, to our knowledge, a complete production process including cell growth and virus production has never been simulated. Here, we demonstrate, for the first time, the amenability of the automated Ambr15 cell culture reactor system to simulate the entire SARS‐CoV‐2 vaccine production process using macrocarriers. To simulate the production process, accessories were first developed to enable insertion of tens of Fibra‐Cel macrocarries into the reactors. Vero cell adsorption to Fibra‐Cels was then monitored and its adsorption curve was studied. After incorporating of all optimized factors, Vero cells were adsorbed to and grown on Fibra‐Cels for several days. During the process, culture medium was exchanged, and the quantity and viability of the cells were followed, resulting in a typical growth curve. After successfully growing cells for 6 days, they were infected with the rVSV‐ΔG‐Spike vaccine virus. The present results indicate that the Ambr15 system is not only suitable for simulating a process using macrocarriers, but also to simulate an entire vaccine production process, from cell adsorption, cell growth, infection and vaccine virus production.